EXO1 overexpression induces homologous recombination deficiency and enhances PARP inhibitor sensitivity in ER-positive breast cancer: modulation by N4BP2L2-Mediated restoration - Sugiyama, Runa; Sedukhina, Anna S.; Sato, Eri; Yamaura, Ayako; Minagawa, Kimino; Pae, Sookhee; Imai, Ena; Chawla, Ankita; Xu, Ziran; Chakraborty, Mihika; Gonoi, Satori; Yamaoka, Jotaro; et al. (Frontiers in Cell and Developmental Biology, 2025)
Exonuclease 1 (EXO1) is a critical enzyme in homologous recombination (HR) and is implicated in cancer progression, with overexpression linked to poor prognosis in multiple tumor types. Yet, the impact of EXO1 overexpression on HR efficiency in estrogen receptor (ER)-positive breast cancer remains unclear. Here, we investigated this using The Cancer Genome Atlas (TCGA) and functional studies in ER-positive T47D cells. High EXO1 expression was associated with elevated homologous recombination deficiency (HRD) scores in ER-positive tumors, indicating impaired HR activity. In T47D cells, EXO1 overexpression reduced HR efficiency, measured by the Advanced Homologous Recombination Assay (ASHRA), and increased sensitivity to the PARP inhibitor olaparib. Using multi-cohort transcriptomic analysis and machine learning interpretability approaches (Random Forest, SHAP, and permutation importance), we identified N4BP2L2 as a key modulator of HR under EXO1 overexpression. Both SHAP and permutation-importance analyses consistently highlighted N4BP2L2 as a strong HR-restorative gene, whereas OTUD7B showed weaker, context-dependent effects. Validation in an independent Korean cohort confirmed N4BP2L2 as a reproducible modulator of HR. Survival analyses across three ER-positive breast cancer cohorts (TCGA, E-MTAB-365, and METABRIC) revealed that high EXO1 expression was associated with shorter survival, whereas concurrent high N4BP2L2 expression mitigated this adverse prognostic effect, even after multivariate adjustment. Functional assays in both T47D and MCF7 cells demonstrated that co-expression of N4BP2L2 restored HR activity and reduced olaparib sensitivity in EXO1-overexpressing cells. These findings suggest EXO1 overexpression serves as a marker of functional HR deficiency and a potential predictor of PARP inhibitor response, highlighting the EXO1–N4BP2L2 axis as a promising biomarker and therapeutic target, especially for guiding PARP inhibitor use beyond BRCA-mutated tumors.